3‐1: A Multi‐plane Volumetric Optical See‐through Head Mounted 3D Display. Issue 1 (May 2016) - Liu, Shuxin; Li, Yan; Li, Xiao; Zhou, Pengcheng; Rong, Na; Yuan, Yachao; Huang, Shuaijia; Lu, Wenqing; Su, Yikai
Abstract : We design an optical see‐through head mounted display (HMD) employing multi‐plane volumetric technique for augmented reality applications. With a stack of fast‐switching polymerstabilized liquid crystal scattering shutters, the HMD provides correct depth information and solves the accommodationconvergence conflict.